2021
DOI: 10.3390/antibiotics10111373
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Candidal Activity of the Parasitic Plant Orobanche crenata Forssk

Abstract: Candida albicans (C. albicans) and Candida glabrata (C. glabrata) are part of the human microbiome. However, they possess numerous virulence factors, which confer them the ability to cause both local and systemic infections. Candidiasis can involve multiple organs, including the eye. In the present study, we investigated the anti-candidal activity and the re-epithelizing effect of Orobanche crenata leaf extract (OCLE). By the microdilution method, we demonstrated an inhibitory effect of OCLE on both C. albican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 114 publications
(127 reference statements)
0
3
0
Order By: Relevance
“…Orobanche crenata (OCLE), a parasitic plant particularly widespread in the Mediterranean area, has shown the ability to inhibit the growth of numerous bacteria and Candida spp. [ 94 ]. D’Angeli et al have shown that OCLE can inhibit the growth of C. albicans and C. glabrata but does not cause death (it has a fungistatic effect).…”
Section: Novel Strategies To Control Biofilm-associated Ocular Infect...mentioning
confidence: 99%
See 1 more Smart Citation
“…Orobanche crenata (OCLE), a parasitic plant particularly widespread in the Mediterranean area, has shown the ability to inhibit the growth of numerous bacteria and Candida spp. [ 94 ]. D’Angeli et al have shown that OCLE can inhibit the growth of C. albicans and C. glabrata but does not cause death (it has a fungistatic effect).…”
Section: Novel Strategies To Control Biofilm-associated Ocular Infect...mentioning
confidence: 99%
“…Nanosystems and alternative compounds for the treatment of fungal infections.Research and development of new drugs is aimed at the study of phytoextracts, which contain a pool of bioactive compounds with different biological activities, including antimicrobial ones. It has been shown that phenolic compounds, isolated from natural sources, have shown anticandidal activity, even if knowledge on the biological properties of various medicinal plants remains limited.Orobanche crenata (OCLE), a parasitic plant particularly widespread in the Mediterranean area, has shown the ability to inhibit the growth of numerous bacteria and Candida spp [94]…”
mentioning
confidence: 99%
“…The elution rate was 300 µL/min for 30 min into a C18 column (Phenomenex Kinetex ® 2.6 µm C18 100 Å, 100 × 2.1 mm, with a volume of injection of 10 µL. To comprehensively assess the analyzed spectrum, ESI-Ms/Ms was used with positive and negative polarities for detailed spectrum analysis, with the equipment settings as previously reported [57]. To quantify the crocin content in each variety of saffron, crocin was properly diluted in water and the calibration curve was constructed in the range 8000 ng/mL-150,000 ng/mL using the software's "Quantitation Wizard" function.…”
Section: Determination Of Crocin Contentmentioning
confidence: 99%